Unleashing the Power of Play: A Digital Hangman Game to Supercharge Arabic Vocabulary - Shahabuddin, Mohd Zaki; Muhammad, Fatimah Noni; Ismail, Zati Hanani; Zulkifli, Muhammad Firdhaus; Rahmi, Zulaida (KnE Social Sciences, 2025)
Learning Arabic as a foreign language often causes challenges for school students because of the significant differences to their mother tongue and the unappealing methods of traditional teaching and learning. This development research of online digital game application aims to develop and evaluate an innovative, simple and interactive learning method by adapting the traditional Hangman childhood game by using web-based application development technology of HTML, JavaScript and CSS. The development methodology of this application involves an iterative process between needs analysis, designing, developing, and testing prototypes to ensure that the game produced is of high quality and hopefully meets the needs of students in improving their mastery of Arabic vocabulary. The Hangman digital game that was developed is expected to overcome non-interactive traditional learning methods, with aim to increase students’ motivation in mastering their Arabic vocabulary. The results of the study are expected to contribute to the field of Arabic education by providing an effective learning alternative that attract school students.